Visualization Analysis of Concrete Incorporating Waste Tire Rubber: A Knowledge Graph Approach - Sameh Fuqaha; Jazaul Ikhsan; Ahmad Zaki (Journal of Civil Engineering, 2025)
The increasing disposal of waste tires presents a global environmental challenge, necessitating innovative recycling solutions. Incorporating waste tire rubber into concrete offers a sustainable approach to mitigating landfill accumulation while promoting eco-friendly construction materials. However, research on rubberized concrete remains fragmented, necessitating a systematic visualization of its evolution, key contributors, and emerging innovations. This study employs a knowledge graph approach to analyze bibliometric data on concrete incorporating waste tire rubber, identifying major trends, research clusters, and influential studies. Using VOSviewer and bibliometric techniques, the study maps the intellectual landscape, revealing a significant rise in publications between 2019 and 2024, with China, India, and Australia leading contributions. Keyword analysis highlights key challenges such as reduced compressive strength, durability concerns, and workability issues, while also identifying solutions like surface treatments and supplementary cementitious materials. Citation analysis indicates that research primarily focuses on mechanical performance and sustainability, underscoring the need for further exploration of long-term durability and large-scale applications. The findings offer valuable insights for researchers and industry professionals, supporting the optimization of rubberized concrete formulations and its broader adoption in sustainable construction.